Changing Patterns of Substance Use During the Coronavirus Pandemic: Self-Reported Use of Tobacco, Alcohol, Cannabis, and Other Drugs - Benschop, Annemieke; van Bakkum, Floor; Noijen, Judith (Frontiers in Psychiatry, 2021)
As in many other countries worldwide, the coronavirus pandemic prompted the implementation of an ‘intelligent lockdown’ in the spring of 2020 in the Netherlands, including the closure of nightlife venues and cancellation of festivals. Such restrictions and social distancing could particularly affect people who use alcohol or other drugs in recreational settings and give rise to new challenges and additional needs in the field of addiction prevention and care. To monitor changes in substance use and provide services with practical directions for tailored prevention, an anonymous web survey was set up, targeting a convenience sample aged 16 years or older through various social media and other online channels. Between May and October 2020, a total of 6,070 participants completed the survey, mainly adolescents and young adults (16-24 years old). These data were used to explore and describe changing patterns in substance use. Overall results showed declined current use compared to ‘pre-corona’, but mask underlying variation in changing patterns, including discontinued (tobacco 10.4%, alcohol 11.3%, cannabis 16.3%, other drugs 30.4%), decreased (tobacco 23.0%, alcohol 29.1%, cannabis 17.4%, other drugs 20.7%), unchanged (tobacco 30.3%, alcohol 21.2%, cannabis 22.3%, other drugs 17.3%), increased (tobacco 29.6%, alcohol 32.1%, cannabis 32.9%, other drugs 25.3%), and (re)commenced use (tobacco 6.7%, alcohol 6.3%, cannabis 11.1%, other drugs 6.2%). Especially the use of drugs like ecstasy and nitrous oxide was discontinued or decreased due to the lack of social occasions for use. Increased use was associated with coping motives for all substance types. As measures combatting the coronavirus may need to be practiced for some time to come, possibly leading to prolonged changes in substance use with lingering ‘post-corona’ consequences, timely and ongoing monitoring of changing patterns of substance use is vital for informing prevention services within this field.